2022
DOI: 10.1126/sciadv.abq3500
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-coordinated mRNA vaccines with enhanced mRNA expression and immunogenicity induce robust immune responses against SARS-CoV-2 variants

Abstract: It is urgent to develop more effective mRNA vaccines against the emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants owing to the immune escape. Here, we constructed a novel mRNA delivery system [IC8/Mn lipid nanoparticles (IC8/Mn LNPs)]with high immunogenicity, via introducing a stimulator of interferon genes (STING) agonist [manganese (Mn)] based on a newly synthesized ionizable lipid (IC8). It was found that Mn can not only promote maturation of antigen-presenting cells via activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…The exploration of LNPs, which carry double‐stranded siRNA for the purpose of knocking down checkpoint inhibitors such as anti‐PD‐L1, indoleamine 2,3‐dioxygenase 1 (IDO), and transcription factor forkhead box P3 (FOXP3), among others, is being investigated for the treatment of cancer, as well as for in vitro engineered DC vaccines 111 . Moreover, the utilization of LNPs for the codelivery of antigen‐encoding‐ and immunomodulatory‐encoding‐mRNA has demonstrated the ability to activate innate immunity through the binding of PRRs expressed by APCs 112‐114 . Additionally, the codelivery of immunomodulatory‐encoding mRNA with siRNA for checkpoint inhibitors was shown to counteract the immunosuppressive TME and achieve potent antitumor efficacy 115,116 .…”
Section: Lipid‐based Nps As Drug Delivery System In Cancer Immunotherapymentioning
confidence: 99%
“…The exploration of LNPs, which carry double‐stranded siRNA for the purpose of knocking down checkpoint inhibitors such as anti‐PD‐L1, indoleamine 2,3‐dioxygenase 1 (IDO), and transcription factor forkhead box P3 (FOXP3), among others, is being investigated for the treatment of cancer, as well as for in vitro engineered DC vaccines 111 . Moreover, the utilization of LNPs for the codelivery of antigen‐encoding‐ and immunomodulatory‐encoding‐mRNA has demonstrated the ability to activate innate immunity through the binding of PRRs expressed by APCs 112‐114 . Additionally, the codelivery of immunomodulatory‐encoding mRNA with siRNA for checkpoint inhibitors was shown to counteract the immunosuppressive TME and achieve potent antitumor efficacy 115,116 .…”
Section: Lipid‐based Nps As Drug Delivery System In Cancer Immunotherapymentioning
confidence: 99%
“…[11] To avoid these cationrelated side effects, non-electrostatic loading strategies driven by other interactions like base complementary pairing, [84][85][86] hydrogen bonding, [87] and coordination have been explored for mRNA delivery. [88,89] For example, forming metal/mRNA complex via metal coordination-mediated self-assembly is a practical strategy to condense mRNA. Zou et al applied Zn 2+ -directed mRNA selfassembly to prepare spherical NPs, which preserved the biological function of mRNA and achieved effective green fluorescent protein (GFP) expression, demonstrating the potential of metal coordination-driven mRNA self-assembly and broaden the application of mRNA-based therapeutics.…”
Section: Mrna Delivery Systemsmentioning
confidence: 99%
“…[170] In addition to inorganic NPs-based hybrid delivery vehicles, other organic-inorganic hybrid vectors also have been employed for mRNA delivery, such as GO-PEI complexes, metalorganic frameworks (MOFs), and metal ion-containing hybrid vector. [56,89,171] Choi et al presented a GO-PEI hybrid vector to deliver mRNA encoding reprogramming transcription factors, in which positively charged PEI can complex mRNA and negatively charged GO can decrease the toxicity of PEI and protect mRNA from degradation. [56] Sun et al developed a dendritic cationic polymer PGMA(EA)-modified zirconium (Zr)based MOF catiomer for mRNA delivery, which improved the stability of mRNA assemblies and enhanced mRNA transfection efficacy compared to linear catiomer.…”
Section: Hybrid Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that LNPs with intrinsic STING activation function induce APC maturation, cytokine expression, and enhanced anti-tumor efficacy (L. Miao et al, 2020). Meanwhile, Fan et al (2022) reported a novel mRNA delivery system (IC8/Mn LNPs) containing a STING agonist (manganese [Mn]), which not only promotes the maturation of APCs by activating the STING pathway, but also improves lysosomal escape to increase mRNA expression. Co-administration of mRNA vaccines and their corresponding adjuvants can significantly enhance the body's immune response to antigens and improve the vaccines' effectiveness (Zhuang et al, 2022).…”
Section: Efficient Delivery Systems To Improve the Delivery Efficacy ...mentioning
confidence: 99%